Fatigue routing of container ships – assessment of contributions to fatigue damage from wave-induced torsion and horizontal and vertical bending - Li, Zhiyuan; Ringsberg, Jonas (Ships and Offshore Structures, 2012)
The traditional method for assessing fatigue damage of ship structures assumes moderate wave amplitudes and linear responses. This method can be questioned when applied on container ships which are characterized by large deck openings that cause low torsion rigidity of the structure. Depending on the heading of the vessel in relation to wave encounter direction, container ships can therefore be sensitive to, for example, oblique waves. In the current investigation, the SESAM software with the three-dimensional hydrodynamic code WASIM is used to simulate a 4400 TEU container ship operating in the North Atlantic. Nonlinear wave loads are utilized for direct calculation of stress histories under severe sea states using the finite element software in SESAM. A method for the separation of normal stress components in an arbitrary cross section and location of the ship is proposed: warping stress from wave-induced torsion, and stress components from horizontal and vertical bending. The strain (stress) response calculated using the models in one location is verified against full-scale measurements made on a similar type of container vessel in the same location. A case study is presented for fatigue damage assessment in two cross sections of the container ship. The contributions to fatigue damage from wave-induced torsion and horizontal and vertical bending are calculated and presented in a fatigue damage routing tool by means of polar diagrams, which includes the effects of heading and ship speed on fatigue damage.